Flirtation walk - Mitchell, Siri L., 1969- (Bethany House, a division of Baker Publishing Group, 2016)
"When a woman trying her best to be good meets a man determined to be anything but, can there be hope for love, or will two lonely hearts be condemned to casual flirtation?"--Back cover.